Professional Identity as a Determinant of the Future Psychologist’ Mental Health - Волошина Valentina Vitalievna (Psychological Prospects Journal, 2012)
Theoretical analysis of the issue of the future psychologists’ professional identity is represented in this article. The need for enrichment of psychological educational training programs with techniques aimed at the development of professional and personal identity according to the future professional activity is argued.